Wellbeing 2014
DOI: 10.1002/9781118539415.wbwell059
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhoods and Social Interaction

Abstract: This chapter examines the relationship of the neighborhood built environment to social interactions, and, ultimately, wellbeing. Beginning with Jane Jacobs's (1961/1992) observations on what she believed were the essential elements of urban neighborhoods, we then review subsequent research on social interactions and health. This is followed by a highlight of research‐validated neighborhood characteristics originally identified by Jacobs that, over the last two decades, have been found to be significant to soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…Regarding the space-society dialectics, findings of this study prove an explicit and strong correlation between land use and outdoor social activities, so that urban areas with mixed land use pattern show higher intensity and density of outdoor social activities. This is consistent with a large number of studies that provide evidence for such a correlation (Brown and Lombard 2014;Duany, Plater-Zyberk, and Speck 2010;Desyllas, Connoly, and Hebbert 2003;Leyden 2003;Grant 2002). The findings, however, do not support environmental determinism or architectural determinism, but advocate the 'opportunistic approach' which, as explained earlier, suggests that spatial layout and physical characteristics of the environment provide or preclude opportunities for interaction and socialisation, but do not cause such to occur.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…Regarding the space-society dialectics, findings of this study prove an explicit and strong correlation between land use and outdoor social activities, so that urban areas with mixed land use pattern show higher intensity and density of outdoor social activities. This is consistent with a large number of studies that provide evidence for such a correlation (Brown and Lombard 2014;Duany, Plater-Zyberk, and Speck 2010;Desyllas, Connoly, and Hebbert 2003;Leyden 2003;Grant 2002). The findings, however, do not support environmental determinism or architectural determinism, but advocate the 'opportunistic approach' which, as explained earlier, suggests that spatial layout and physical characteristics of the environment provide or preclude opportunities for interaction and socialisation, but do not cause such to occur.…”
Section: Resultssupporting
confidence: 84%
“…They either use the high street for shopping and socialising purposes, or prefer quiet and non-traffic places inside the urban blocks where they feel safer and more comfortable. It has been widely argued that mixed land use promotes social life in urban space (Brown and Lombard 2014;Duany, Plater-Zyberk, and Speck 2010;Welsh and Farrington 2009;Grant 2002). Overlapping outdoor social activity maps with mixed land use map would be helpful to examine these arguments in the case study neighbourhoods.…”
Section: Spatial Pattern Of Activity Typementioning
confidence: 99%
“…Mass et al (2009) suggested that abundant green space in the living environment could enhance residents' feelings of social safety, but the opposite effect was observed in highly dense areas [42]. Brown and Lombard (2014) discovered that a variety of retail and public facilities made neighborhoods more interesting and recognizable [43]. Residents accordingly found more opportunities to chat with friends nearby and improve their sense of belonging and well-being.…”
Section: Built Environment Perceived Disorder and Mental Healthmentioning
confidence: 99%
“…From a cognitive perspective, informal social contacts help residents build solid social ties with community members. This conscious or unconscious social support leads to the creation of a friendly neighborhood atmosphere with high levels of trust and reciprocity, protecting residents from pathological mental states such as depression and anxiety [43]. From a structural perspective, frequent behavioral interactions are a prerequisite for strong social cohesion and collective efficacy-both of which relate to translating individual social ties into collective common goals to combat health risks [47].…”
Section: Built Environment Social Interaction and Mental Healthmentioning
confidence: 99%
“…Neighboring facilitates the promotion of services and amenities between neighborhood residents, positively impacting health (Kawachi & Berkman, ). Social support derived from neighboring enhances life satisfaction and well‐being (Brown & Lombard, ). Social support is also critical in promoting positive health and mental health over the life course (Cohen & Willis, ).…”
Section: Introductionmentioning
confidence: 99%